2015
DOI: 10.1093/ecco-jcc/jjv129
|View full text |Cite
|
Sign up to set email alerts
|

Disease Outcome of Ulcerative Colitis in an Era of Changing Treatment Strategies: Results from the Dutch Population-Based IBDSL Cohort

Abstract: Over the past two decades, a reduction in early colectomy rate was observed, with no further reduction in the most recent era. Late colectomy rate and hospitalisation rate remained unchanged over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 42 publications
13
55
0
Order By: Relevance
“…The 5-year probability of surgery fell from 7.5 to 4.1% in the population diagnosed during the periods 1991-1997 and 2001-2006 respectively. No change in surgical indication over the time was observed [9] . In contrast, a cohort study of all hospitalizations for UC in Calgary Health Zone during a period 1997-2009 found a decrease in elective colectomies only, while the rate of emergent surgeries remained stable [10] .…”
Section: Ulcerative Colitismentioning
confidence: 91%
See 3 more Smart Citations
“…The 5-year probability of surgery fell from 7.5 to 4.1% in the population diagnosed during the periods 1991-1997 and 2001-2006 respectively. No change in surgical indication over the time was observed [9] . In contrast, a cohort study of all hospitalizations for UC in Calgary Health Zone during a period 1997-2009 found a decrease in elective colectomies only, while the rate of emergent surgeries remained stable [10] .…”
Section: Ulcerative Colitismentioning
confidence: 91%
“…In a national Danish cohort study , the cumulative probability of colectomy at 9 years decreased from 14.5% in a cohort diagnosed 1979-1994 to 9.1% in patients diagnosed after the year 1994 [4] . Likewise, a Dutch population-based study of UC patients diagnosed during 1991-2010 demonstrated a decline in colectomy rate within that time period [9] . The 5-year probability of surgery fell from 7.5 to 4.1% in the population diagnosed during the periods 1991-1997 and 2001-2006 respectively.…”
Section: Ulcerative Colitismentioning
confidence: 98%
See 2 more Smart Citations
“…There is significant morbidity and mortality associated with active UC. Recent cohort studies estimate that 4.1-14.8% of patients with UC undergo colectomy during their disease course [Solberg et al 2009;Targownik et al 2012;Jeuring et al 2015]. For years, management primarily included the use of 5-aminosalicylates, corticosteroids, azathioprine, and surgery.…”
Section: Introductionmentioning
confidence: 99%